TINJAUAN VISUAL DESAIN KEMASAN DAN SAMPUL ALBUM BAND INDIE MOCCA PADA ALBUM BERFORMAT AUDIO CD - AYYUB ANSHARI SUKMARAGA; IMAN SUDJUDI; SUSANTO SUSANTO (Serat Rupa: Journal of Design, 2016)
For five decades, music industry has become profitable business. The big music industries then make innovation with attractive packaging design for cover album. The innovation intended to persuade people to buy the album not just listen to musics by downloaded it, although it can’t reduce music piracy that become giant problems for music industries. One of Indonesian indie band that aware for this activities is Mocca.This research is analyzing an how the visual perception of shape, structure, material, color and elements in Mocca’s CD packaging and album cover’s design, can create visual sensation to people. It is analyze people’s interpretation from the typography in Mocca’s packaging design and cover album. The aim of this research is to identify symbols, sensation, layout, and people’s interpretation from Mocca’s albums. For the result on this research, will compared by the respondents result through semantic’s theory as will be verified using the results of the analysis of rhetoric. The result from this research is shown that use of the visual system in Mocca’s packaging and design album covers can impact the visual sensation and persuade people when they see visual markings on Mocca’s packaging as well as the album covers. Mocca’s CD quality can compete with band from big music companies. This Mocca’s success from their packaging design dan cover albums art could be the example for other band or music industries to gain their value in art, so it will give better product sales. Keywords: cover; indie band; packaging; visual analysis; rhetoric analysis